Comparison of five indices for prediction of adverse outcomes in hospitalised Mexican older adults: A cohort study. Issue 1 (January 2015) - Dent, Elsa; Perez-Zepeda, Mario
Highlights Predictive tools of adverse outcomes in elderly are necessary. The Frailty Index predicts adverse outcomes in diverse settings. Predictive tools could help in settings with scarce specialized resources. The Frailty Index was found to predict long length of stay. Using these tools could help in decision making.